Seed structure and localization of reserves in Chenopodium quinoa - Prego, Imelda (1998)
The three areas of food reserves in quinoa seeds are: a large central perisperm, a peripheral embryo and a one to twocell layered endosperm surrounding the hypocotyl-radicle axis of the embryo. Cytochemical and ultrastructural analysis revealed that starch grains occupy the cells of the perisperm, while lipid bodies, protein bodies with globoid crystals of phytin, and proplastids with deposits of phytoferritin are the storage components of the cells of the endosperm and embryo tissues. EDX analysis of the endosperm and embryo protein bodies revealed that globoid crystals contain phosphorus, potassium and magnesium. These results are compared with studies on other perispermous seeds published to date.